The Expression of Drought Resistance GmDREB-1 Gene on Soybean (Glycine max L. Merr) as Result of EMS Mutation Induction (Etyl Methane Sulfonate) - Sandi Savitri, Evika; Siti Resmisari, Ruri (International Journal of Engineering and Technology, 2019)
Abiotic stresses, particularly drought, are harmful for the plant productivity. Mutagenesis is widely used as method that is potential to increase the variability of crop development. Mutagenic using EMS (Ethyl Methane Sulfonate) shows more effective results than using other mutagens. DREB1 gene is a subclass of DREB gene which is a transcription factor and it also serves as a key regulatory response of plants to drought stress. Mutation induction combines concentration treatment and immersion time in EMS.Â RNA isolation employs RNeasy Plant Mini Kit (Qiagen). GmDREB-1 expression is analyzed using Real Time PCR (Quantitative Real-time Polymerase Chain Reaction or Q-PCR). The analysis shows that mutation treatment with EMS using 0.07% concentration with a wide range of immersion time indicates that GmDREB-1 expression is higher than other treatments.Â The results of this study proved that mutation induction using EMS can be used as an alternative to plant breeding to obtain drought resistant soybean.Â Induction mutation useful for improvement genetic variability of plant.Â Â